Manajemen Husemas Berbasis OBE dalam Mengoptimalisasi Kurikulum Merdeka di Lahan Basah - Hauna Shafiya; Adelia Arlina Julianty; Patianor Habibah; Maulidhia Ayu Saputri; Hellawati; Nor Sri Yulida; Suhaimi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the management strategy of School-Community Relations (Husemas) based on Outcome-Based Education (OBE) in optimizing the Merdeka Curriculum within the wetland ecosystem. Using a library research method, data were gathered from various reputable journals and relevant policy documents. The results indicate that integrating OBE principles through POAC management functions can align curriculum flexibility with measurable competency outcomes. The synergy of the Tri-Center of Education involving families and the community, along with the internalization of local wisdom such as the Balampah tradition, serves as a key factor in overcoming geographical barriers in aquatic regions. In conclusion, professional Husemas management can transform wetland environmental challenges into contextual learning resources that enhance graduate quality. Abstrak Keywords: School-Community Relations Management, Outcome-Based Education (OBE), Merdeka Curriculum, Wetlands, Educational Synergy. Abstrak Penelitian ini bertujuan untuk menganalisis strategi manajemen Hubungan Sekolah dan Masyarakat (Husemas) berbasis Outcome-Based Education (OBE) dalam mengoptimalisasi Kurikulum Merdeka di ekosistem lahan basah. Menggunakan metode studi literatur, data dikumpulkan dari berbagai jurnal bereputasi dan dokumen kebijakan terkait. Hasil penelitian menunjukkan bahwa integrasi prinsip OBE melalui fungsi manajemen POAC dapat menyelaraskan fleksibilitas kurikulum dengan kebutuhan luaran kompetensi yang terukur. Sinergi Tri Pusat Pendidikan yang melibatkan keluarga dan masyarakat, serta internalisasi kearifan lokal seperti tradisi Balampah, menjadi faktor kunci dalam mengatasi hambatan geografis di wilayah perairan. Kesimpulannya, manajemen Husemas yang profesional mampu mentransformasi tantangan lingkungan lahan basah menjadi sumber belajar kontekstual yang meningkatkan kualitas lulusan. Kata Kunci: Manajemen Husemas, Outcome-Based Education (OBE), Kurikulum Merdeka, Lahan Basah, Sinergi Pendidikan.